Equitable suicide prevention for youth impacted by the juvenile legal system - Meza, Jocelyn I.; Snyder, Sean; Shanholtz, Caroline (Frontiers in Psychiatry, 2022)
Suicide is the second leading cause of death for adolescents in the United States. Despite the already alarmingly high rates of suicide attempts among adolescents, youth involved in the juvenile legal system are up to three times more likely to have suicide attempts than their peers not impacted by the juvenile legal system. This public health crisis is also a matter of health equity, knowing that ethnoracially minoritized youth, mainly Black and Latinx youth, have disproportionate contact with the juvenile legal system. In order to disrupt the current elevated rates of suicide among Black and Latinx youth involved in the juvenile legal system, there needs to be more concerted efforts to improve assessment and suicide prevention efforts in the juvenile legal system. There are various potential touch points of care for suicide prevention and the Sequential Intercept Model, which outlines community-based responses to the involvement of people with mental and substance use disorders in the criminal justice system, can be used as a strategic planning tool to outline possible equitable interventions across these various touch points. Our purpose is to provide a comprehensive picture of gaps and equitable opportunities for suicide prevention across each intercept of the Sequential Intercept Model. We provide recommendations of priorities to promote health equity in suicide prevention for ethnoracially minoritized youth impacted by the juvenile legal system.